14/3-34r/3=-4/3(10r-2)

Simple and best practice solution for 14/3-34r/3=-4/3(10r-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14/3-34r/3=-4/3(10r-2) equation:


r in (-oo:+oo)

14/3-((34*r)/3) = (-4/3)*(10*r-2) // - (-4/3)*(10*r-2)

14/3-((-4/3)*(10*r-2))-((34*r)/3) = 0

(4/3)*(10*r-2)+(-34/3)*r+14/3 = 0

4/3*(10*r-2)+(-34*r)/3+14/3 = 0

(4/3*3*(10*r-2))/3+(-34*r)/3+14/3 = 0

4/3*3*(10*r-2)-34*r+14 = 0

6*r-8+14 = 0

6*r+6 = 0

(6*r+6)/3 = 0

(6*r+6)/3 = 0 // * 3

6*r+6 = 0

6*r+6 = 0 // - 6

6*r = -6 // : 6

r = -6/6

r = -1

r = -1

See similar equations:

| 25/3=28a/3-4(4a/3-1/3) | | 6q/5+2(-1+2q/5)=0+10q | | -4*(x+8)+14=7*(x-2)+29 | | 8(0)-3y=72 | | -p/3+2/3(-1+9p)=2-3/3+2p/3 | | 4x1/8 | | 5x+27=-9*(x-10)+7 | | 8x-3(0)=30 | | x=8/3y | | 5h=12.50 | | 12x+2*(x-3)=7*(x-5)+1 | | -2(x+2)=-2x-3-1 | | 6x-2x^2-24x^4= | | (e^7x)=11 | | -(2x+10)+8=4*(-x+1) | | 14(n-6)=14n-32 | | 3x-4*(x-2)+2x=1 | | 4x-7=12x-50 | | 7x=23-3x | | -32-5(7*7-10*10)= | | -32-5*7*7-10*10= | | x-15=-57 | | x+19=54 | | 4x-5=7x+15 | | 5x+12=6x+17 | | m=8+4n | | 88*x+44=8*x-116 | | 6x*5=3 | | 4x/5=4 | | 4x/5=4x | | 4*4-3*4-6= | | -3y=6x-9 |

Equations solver categories